تأثير إضافة طلع النخيل إلى العلف في إنتاجية البيض وصفات الفقس لطائر السمان الياباني (Coturnix japonica) /Effect of Adding Date Palm Pollen on Egg productivity and hatching traits of Japanese quail birds (Coturnix japonica) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
This study was conducted at quail's field of Agriculture Collage/ University of Basrah for the period from 5/10/2016 to 5/12/2016 to examine the effect of adding Date Palm Pollen to feed on some Egg productivity and hatching traits of Japanese quail birds. The study was included (180) birds of brown quail birds at the age of sexual maturity (after 45 days). They were randomly distributed to five treatments each treatment contained 36 birds with three replicates each one 12 birds, the treatments as the following, the first groups (T1) were fed on basal diet without feed additive and regarded as control mean, while the 2nd groups (T2), the 3rd groups (T3), the 4th groups (T4) and the 5th groups (T5) In these treatments, were fed on a diet supplemented the Date Palm Pollen (250, 500, 750 and 1000 mg/kg) Respectively. The results showed a significant increase in the percentage of egg production and the number of eggs cumulative and weight of eggs and the mass and thickness of eggshell for added treatments (T3, T4, and T5) compared to control treatment T1 at age 30 and 60 days, There was a significant increase in fertility rate, Hatchability rate, and weight of chick hatch of the T5 treatment compared to other treatments, as well as a significant decrease in the embryo mortality rate at the age of 30 and 60 days after sexual maturity. In conclusion, the Date palm pollen was improved of Egg productivity as well as hatching traits of Japanese quail.